The Transformation of Labour Managed Monopoly: Competition Policy Versus Mixed Firms - Gianpaolo Rossini; Carlo Scarpa (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1991)
Starting from a market monopolized by a two plant labour-managed (LM) firm, we consider alternative ways to reduce the inefficiencies associated with this market arrangement. The first possibility is the creation of a duopoly, in which a plant is turned into a LM firm, while the other one is either LM, or is managed to maximize profits. The second one is the negotiated creation of a "mixed firm", managed by workers and Government representatives. Its objective function reflects the different goals of its participants. Welfare comparisons purport the mixed duopoly as the preferable solution.
Keywords: 330